Family Coping Strategies to Improve the Health of Family Members Living with Schizophrenia - Sugeng Mashudi; Ah Yusuf (Universitas Airlangga, 2021)
Introduction: Schizophrenia is a serious mental illness that affects the thinking, emotions, relationships, and decision-making. One of the positive effects of treating schizophrenia in patients is family health. The family welfare management strategies provide help for coping, care preparation, organizing meetings, and mentoring. This study focuses on family coping strategies for improving the health of members living with schizophrenia.Methods: A cross-sectional design was used by choosing 160 respondents randomly. The inclusion criteria were family members accompanying control schizophrenia patients to the Public Health Center, with a minimum age of 18. The independent variable was family coping, which consist of two sub-variables (problem-focused coping mechanism and emotion-focused coping mechanism), while the dependent variable was family health, which consists of three sub-variables (efficient, satisfaction, and happiness). The SMART PLS (2.0 Version) was used to prove the impact of the variables.Results: The results indicated that family coping had a significant impact on the health of the family. The hypothesis was taken from the value of the T-test on the structural model analysis, which shows T- statistics (13.966) > T-critical (1.96). The impact of family coping on the health is equal to 0.682 (OR). This means that if family coping is given one-unit value, it will increase the family health by 0.682 times.Conclusion: The implementation of the family coping strategy will improve the capacity of the family to clarify health issues encountered, resolve family behaviors effectively and minimize risk factors. Furthermore, the coping mechanisms chosen by families in facing stress will have an impact on the reduction of illness symptoms in the members with schizophrenia.